The rooting of foreign prisoners: Beyond a criterion limiting the expulsion - García-España, Elisa (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2018)
The control migration policy conditions the criminal response when the offender is a foreigner according some experts, and also the response to the foreigner in the penitentiary area. The 2015 reform of art. 89 of Criminal Law introduces the situation of rooting of the foreign person as a limiting element of expulsion. It  is proposed to consider the material concept of rooting with other purposes. In Spanish prisons, the number of foreign prisoners on whom expulsion does not fit is significant. Through a broad concept of rooting, understood as limiting expulsion in the criminal sphere and as a factor of protection against crime, we reflect on the treatment and regime of penitentiaries aimed at the reintegration of convicted aliens.
Keywords: criminal foreigners; prison; root; deportation; reintegration